Effects of SGLT2 inhibitors on hemoglobin levels in patients with chronic kidney disease: A bibliographic review - Ocampo-Rojas, Criss (2024)
Chronic Kidney Disease (CKD) is a progressive condition characterized by structural and functional abnormalities in the kidneys that persist for at least 3 months and are not reversible. With a global prevalence of 11% to 13% and 11% in Peru, CKD is a silent disease that can lead to complications such as anemia due to the shortened lifespan of red blood cells, alterations in iron metabolism, and reduced erythropoietin. The use of sodium-glucose cotransporter type 2 inhibitors (SGLT2 inhibitors) has sparked interest in CKD management. Studies such as DAPA-CKD and EMPA-KIDNEY have shown that SGLT2 inhibitors improve renal and cardiovascular parameters, increasing hemoglobin levels by 0.6 g/dl. This effect is attributed to improved erythropoiesis and efficient iron utilization through hepcidin reduction. Additionally, these inhibitors reduce oxidative stress and improve nitric oxide availability, contributing to hemoglobin increase. In summary, SGLT2 inhibitors are a promising treatment for CKD patients due to their nephroprotective and cardiovascular effects, as well as their ability to increase hemoglobin levels, helping to reduce complications and improve patients' quality of life.